The dose-response relationship of leucine on food cravings, appetite and mood in young men on intermittent fasting - Lee, Yi Shin (Nanyang Technological University, 2020)
Background: Weight loss (WL) quality is as important as quantity. Maximizing muscle retention during WL is key and leucine (Leu) has been identified as a key contributor. Further, food cravings, appetite sensations and mood are associated with WL diet success. However, the effects of Leu dose on these variables are not clear. Purpose: To investigate if there is a dose-response relationship of Leu on changes in body mass, appetite markers, food cravings and mood, after a 4-week alternate day fasting (ADF) intervention in Asian males with body mass index (BMI) ≥ 23 kg/m2. Methods: A parallel, four-arm, double-blinded, randomized controlled trial design was utilized, where 22 participants were allocated into 4 groups receiving 0.02-0.08 g/kg BW/d of Leu. Participants went through 4 weeks of ADF, with a 25% daily caloric deficit. Changes in body mass were measured using a weighing scale, appetite markers with visual analogue scales, food cravings with the Food Craving Questionnaire-Trait-reduced and mood with the Brunel Mood Scale (BRUMS), pre- and post-intervention. Results: Only significant decreases in body mass, appetite markers and the BRUMS vigour subscale scores were observed after the 4-week ADF intervention (mean = -3.69 kg; -7.79 mm; 1.58 arbitrary units, respectively). However, there was no effect of increasing Leu dosage on these observed differences. No differences were observed in the other variables. Conclusions: There is no dose-response relationship of Leu on changes in body mass, appetite markers, food cravings and mood after a 4-week ADF intervention in Asian males with BMI ≥ 23 kg/m2.